SETTLEMENT OF ONLINE CHILD SEXUAL EXPLOITATION CASES IN INDONESIA (CASES STUDY: FACEBOOK GROUP ‘CLUB BRONDONG PUNCAK’ AND ‘OFFICIAL CANDY’S GROUP’) - Kristiningsih, Diah; Kasuma, Iva (PEOPLE: International Journal of Social Sciences, 2018)
This research aims to analyze the implementation of the Law No. 10 Year 2012 regarding the Legalisation of the Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography within the Indonesian legal system on the settlement of the cases of child online sexual exploitation. This research will be conducted by studying two cases of child online sexual exploitation in Indonesia which are: child online prostitution practiced through Facebook group Club Brondong Puncak and child pornography materials distributed through Facebook group Official Candy’s Group. This is a qualitative research through feminist legal theory approach that would reveal the child protection problems in accordance with the analyzed case. Data would be gathered from studying literatures, field study through cyber observation, and interviewing some key resource persons such as the Cyber Crime Unit of the Indonesian Police and the Commission of the Women Empowerment and Child Protection. This research finds the problems related to settling the case of child online sexual exploitation are borne out of a faulty legal framework, a lack of legal knowledge and awareness of the issue, obstacles in obtaining an updated data, insensitivity towards the child’s best interest, and other issues. The Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography legalised under the Indonesian Law No. 10 Year 2012 that could maximize child protection is not being properly integrated within the national legal framework. Hence, there are several legal vacuums that unabling the law enforcers to protect the child victims of online sexual exploitation effectively.